Anaerobic Co-Digestion: A Way to Potentiate the Synergistic Effect of Multiple Substrates and Microbial Diversity - Mariana Ferdeș; Gigel Paraschiv; Mariana Ionescu; Mirela Nicoleta Dincă; Georgiana Moiceanu; Bianca Ștefania Zăbavă (Energies, 2023)
In this paper, the latest research in the field of anaerobic co-digestion related to the advantages of using different mixtures of substrates on the performance of the process and increasing its efficiency is reviewed. The main aspects presented in this review refer to the study of the most commonly used types of substrates, highlighting their characteristics, the diversity of microbial communities involved in the production of biogas, the applied pretreatments, and the possibility of obtaining an improved digestate as a secondary product. The main types of substrates used in anaerobic co-digestion are food waste, sewage sludge, animal manure, lignocellulosic biomass, algae, fats, oils, and greases. The data from the studied works demonstrated that the anaerobic co-digestion process improves the carbon/nitrogen ratio and nutrient balance, increases the process stability, and diminishes the concentration of toxic inhibitors. At the same time, the use of appropriate mixtures of substrates leads to an increase in the diversity of microbial communities, among which synergistic relationships are established that ultimately favor the growth of the methanogenic potential. Finally, based on the research results found, one of the main trends is the need to adapt technology to the type of substrate and the industry.